2019
DOI: 10.1037/rep0000280
|View full text |Cite
|
Sign up to set email alerts
|

Validity of sitting time scores from the International Physical Activity Questionnaire–Short Form in multiple sclerosis.

Abstract: The current study examined the validity of scores from the sitting time item on the International Physical Activity Questionnaire-Short Form (IPAQ-SF) in a sample of persons with multiple sclerosis (MS). Method: Persons with MS were recruited through the distribution of printed letters to a random sample of 1,000 persons from the North American Research Committee on MS registry. Two hundred ninety-five persons with MS were interested and volunteered to wear an ActiGraph accelerometer for a 7-day period and com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…If we compare the time spent sitting down per week collected with the IPAQ of our sample with the study carried out by Moti et al [33], which analyzed people with MS in America, we find that our population has a slightly higher value. Furthermore, our data show elevated levels of physical activity.…”
Section: Discussionmentioning
confidence: 72%
“…If we compare the time spent sitting down per week collected with the IPAQ of our sample with the study carried out by Moti et al [33], which analyzed people with MS in America, we find that our population has a slightly higher value. Furthermore, our data show elevated levels of physical activity.…”
Section: Discussionmentioning
confidence: 72%
“…This was indicated by a reduction in self-reported sitting time on the IPAQ and device-measured sedentary behavior. These results are consistent with those from a recent study that demonstrated the validity of the sitting item from the IPAQ in people with MS. 35 Our secondary outcomes examined change in physical activity. There was a moderate treatment effect on physical activity, indicated by an increase in exercise participation measured via the GLTEQ.…”
Section: Discussionmentioning
confidence: 99%
“…The exposures/activities and outcomes were self-reported and may be affected by recall bias and misclassification. However, previous studies suggested that data from self-reported measures on sitting time and sleep duration were comparable to those from objective measures (Jackson et al, 2018;Motl et al, 2019). Moreover, the exposure variables were collected before the outcomes occurred in the study, which may mitigate the concern about self-reported data and may enhance the study F I G U R E 3 Adjusted odds ratios of changes in activities among pre-, mid-and late pregnancy for Caesarean delivery, medically indicated Caesarean delivery and small for gestational age.…”
Section: Limitationsmentioning
confidence: 93%
“…To measure sitting time, we used structured questions similar to those used in the previously validated "sitting questions" of the IPAQ (Motl, Sasaki, Cederberg, & Jeng, 2019): "How many hours were spent on sitting (on average) in a weekday/weekend during the last 2 weeks, including any types of screen viewing?" Since no previous research has identified a standard cut-off point to determine categories for sitting time in pregnancy, sitting time was stratified into two categories based on the median value of mid-and late pregnancy in this study (<8 or ≥8 hr).…”
Section: Sitting Timementioning
confidence: 99%